The role of friendship in the formation and development of entrepreneurial teams and ventures. Issue 2 (16th May 2016) - D'hont, Laura; Doern, Rachel; Delgado García, Juan Bautista
Abstract : Purpose: – The purpose of this paper is to examine the potential influence of friendship on entrepreneurial teams (ETs) and on venture formation and development. The theoretical framework is built on the literature around friendship ties, the interaction of friendship ties and professional ties, and ETs. Design/methodology/approach: – Taking an interpretative methodological approach, the authors carried out qualitative interviews with ten business founders in Paris, France. Findings: – The authors identified different four profiles or types of ETs according to how friendship ties interact with professional ties among team members, which the authors designate as "fusion" and "separation", and describe the orientation of this interaction, which the authors label as "affective" or "strategic". These profiles affect the emergence of the idea and the choice of members in the formation of teams. They also shape the functioning of teams in terms of decision-making processes, recruitment and investment. Research limitations/implications: – The findings underline the difficulties of studying friendship in ETs empirically and recommend longitudinal approaches for further research. Practical implications: – Findings offer insights in to why and how ETs based on friendship ties approach the pre-launch, launch and development phases of businesses as well as in to the interactions between professional and friendship ties, which is helpful to both practitioners and academics. The authors also discuss the consequences and implications of the different team types in terms of their risks and strategies for mitigating these risks. Originality/value: – This is one of the first empirical studies to examine how friendship and professional ties may combine and evolve in ETs, and their influence on the entrepreneurial process as it relates to venture formation and development.